2018
DOI: 10.1021/acssuschemeng.8b00766
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Nanoplastics in Marine Larvae: A Case Study Using Barnacles, Amphibalanus amphitrite

Abstract: The exposure of nanoplastics was investigated by observing their interaction with Amphibalanus amphitrite (commonly known as acorn barnacles). Poly­(methyl methacrylate) (PMMA) and fluorescent perylene tetraester (PTE) dye were used to prepare highly fluorescent nanoplastic particles. At concentrations of 25 ppm, the PMMA particles showed no detrimental impact on barnacle larvae and their microalgae feed, Tetraselmis suecica and Chaetoceros muelleri. PMMA nanoplastics were ingested and translocated inside the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(41 citation statements)
references
References 51 publications
(79 reference statements)
4
35
0
Order By: Relevance
“…Several laboratory studies have shown that nanoplastics (below 1 µm following the classification from Hartmann et al, 2019) may cause both chemical and physical impacts to marine wildlife. In the last decade (2009-2019), PS NPs have been adopted in 85% of the ecotoxicity studies (n = 41, listed in Supplementary Material), alongside with other polymers, mainly polymethyl methacrylate (PMMA) NPs (Bhargava et al, 2018;Brandts et al, 2018) and polyethylene (PE) nano-sized fragments (Baudrimont et al, 2019). Functionalized PS NPs, such as PS-COOH and/or PS-NH 2 , have been used in 44% of them to correlate the biological effects observed in the functionalization.…”
Section: Effects On Marine Organismsmentioning
confidence: 99%
“…Several laboratory studies have shown that nanoplastics (below 1 µm following the classification from Hartmann et al, 2019) may cause both chemical and physical impacts to marine wildlife. In the last decade (2009-2019), PS NPs have been adopted in 85% of the ecotoxicity studies (n = 41, listed in Supplementary Material), alongside with other polymers, mainly polymethyl methacrylate (PMMA) NPs (Bhargava et al, 2018;Brandts et al, 2018) and polyethylene (PE) nano-sized fragments (Baudrimont et al, 2019). Functionalized PS NPs, such as PS-COOH and/or PS-NH 2 , have been used in 44% of them to correlate the biological effects observed in the functionalization.…”
Section: Effects On Marine Organismsmentioning
confidence: 99%
“…Recent ecotoxicity studies have shown that polystyrene nanoparticles/nano-spherules (PS NPs) cause mild to severe impacts on a range of organisms often as a function of surface functionalization (Della Torre et al 2014;Canesi et al 2015Canesi et al , 2016Bergami et al 2016Bergami et al , 2017Manfra et al 2017;Pinsino et al 2017;Marques-Santos et al, 2018;Mishra et al, 2019). Several studies have also reported the ingestion of nanoplastics in euryhaline and marine zooplankton (Della Torre et al 2014;Manfra et al, 2017;Bhargava et al, 2018;Tallec et al, 2018) under laboratory-controlled conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Ingestion of microplastics represents an environmental concern for the health of the individual as well as for the trophic transfer of plastic contaminants to larger predators as in the case of transfer from algae, to zooplankton, and fish [21,22]. Small nanoplastics were found to directly absorb through the intestinal wall of mussels [20] and bioaccumulate in barnacles [23]. Evidence of plastic particles in the terrestrial environment confirm nanoplastic uptake by plants, earthworms, and in air pollution or aerosolized particulate matter [24].…”
Section: Toxicitymentioning
confidence: 99%